Pemanfaatan Urin Sapi pada Setek Batang Tanaman Jarak Pagar (Jatropha curcas L.) - Ardian '; Murniati ' (Universitas Riau, 2007)
Jarak pagar (Jatropha curcas L.) is one of biodiesel resources with high oil content of 35 to 45%. It can grow up in vegetative and generative way. Growth of this plant could be enhanced by giving natural Plant Growth Regulator (PGR) such as cow’s urine which is easy to take, easy to apply, and cheaper than other materials. PGR will be useful for plant if given in low concentration, but in high concentration it will damage the plant. This research aimed to know influence of interaction of storage period and urine concentration to the plant’s growth. It used randomized factorial block experiment with two factors and three replications. The two factors were: (1) storage time of urine (8, 12, and 16 days), and (2) cow’s urine concentration of 25, 50, 75, and 100%.Key Word : cow's urine, jarak pagar, Jatropa cuircas